Antibacterial activity of Zataria multiflora essential oil and its main components against Pseudomonas aeruginosa - Mahboubi Mohaddese; Heidarytabar Rezvan; Mahdizadeh Elaheh (Herba Polonica, 2017)
Introduction: In Iranian traditional medicine, Zataria multiflora Boiss (Lamiaceae family) is reputed due to its antiseptic effects. Objective: The purpose of this study was to evaluate the antibacterial and biofilm killing effects of Z. multiflora essential oil and main components against Pseudomonas aeruginosa. Methods: The main components of essential oil were identified by gas chromatography (GC) and gas chromatography-mass spectrometry (GC-MS). The antibacterial properties of Z. multiflora oil and main components were determined by assessing the MIC and MBC values, and their inhibition percent of biofilm killing effects were determined by the evaluation of optical density. The role of each main component in these activities was determined according to the chemical profiles of essential oil. Results: Thymol (38.7%), carvacrol (30.6%), and p-cymene (8.3%) were main components of twenty five components of essential oil. Carvacrol had the higher role in antibacterial activity against P. aeruginosa, followed by thymol. P-cymene enhanced the antibacterial activities of thymol and carvacrol against P. aeruginosa. Carvacrol showed the weak role in biofilm killing effect. In spite of the low antibacterial activity of p-cymene against P. aeruginosa, it can enhance the antibacterial activity of thymol or carvacrol. Conclusion: Z. multiflora essential oil can be used for the management of P. aeruginosa infections. Determining the precise role of each components needs investigating in their behavior in different media.